The potential of emerging technologies for safety and health management in the Malaysian construction industry - Lim, Kar Fai (2022)
Traditional safety management was no longer adequate for modern and complex construction projects. In addition, construction workers were exposed to higher health risks than in other industries. Therefore, the objective of this study was to identify the adoption benefits, adoption barriers and willingness to use emerging technologies for safety and health management, which further exposed the potential of implementing emerging technologies for safety and health management in the Malaysian construction industry. Besides, this study used a questionnaire survey and quantitative research methods to complete the data collection and analysis. Moreover, the target respondents were the Grade 7 main contractors in Malaysia, with 392 respondents participating in this study, achieving a response rate of 49%. According to the results of the mean ranking, the most significant benefits contractors perceive to be gained from using emerging technologies for safety and health management were Enhance Hazard Identification, Improve Safety Planning and Intensify Safety Inspection. Beyond that, the most prominent barriers to using emerging technologies in safety management were Extra Costs, Additional Training and Lack of Top Management Support. Furthermore, the top emerging technologies that G7 contractors were willing to use to improve safety and health management were Building Information Model, Wearable Safety Technology and Unmanned Safety Technology. The correlation and regression analysis results further revealed that the adoption benefits of emerging technologies were more influential than the adoption barriers of emerging technologies, thus confirming that the implementation of emerging technologies for safety and health management in the Malaysian construction industry had positive potential. Finally, the findings of this study provided an impetus for the public and private sectors to offer incentives and initiate action to remove any barriers to the generalisation of emerging technologies in safety and health management. Meanwhile, the results of this study extended the existing literature, which could increase awareness and knowledge of construction practitioners in the use of emerging technologies for safety and health management.